Alliance claims land: post guards on 500,000 acres (Raton, New Mexico Raton Range, 1966)
The dispute between the government and Spanish - Americans claiming title to 500,000 acres of federal land in northern New Mexico slowed today to strategy sessions.
A newspaper article on the dispute between the government and Spanish Americans claiming title to 500,000 acres on federal land
Master list item # 2
File location is in the New Mexico Cities and Towns
Keywords: Abiquiu, New Mexico; Carson National Forrest Lands; Rio Arriba County; Federal Alliance of Land Grants; 500,000 acres federal land